Agricultural land in Myanmar’s dry zone - Hein, Aung; Lambrecht, Isabel B.; Lwin, Kyaw; Belton, Ben (Michigan State University, 2017)
In this research highlight, we present analysis of agricultural land use, distribution, access, tenure, land markets, and historical patterns of ownership and disposal. Findings are derived from a representative survey of 1578 rural households in Myanmar’s Central Dry Zone - the Rural Economy and Agriculture Dry Zone Survey (READZ). The READZ survey was conducted from April to May 2017 in four townships (Magway, Pwinbyu, Myittha, and Budalin) in Magway, Mandalay and Sagaing regions.